Internalization of paramagnetic phosphatidylserine-containing liposomes by macrophages - Geelen Tessa; Yeo Sin; Paulis Leonie EM; Starmans Lucas WE; Nicolay Klaas; Strijkers Gustav J (Journal of Nanobiotechnology, 2012)
Abstract Background Inflammation plays an important role in many pathologies, including cardiovascular diseases, neurological conditions and oncology, and is considered an important predictor for disease progression and outcome. In vivo imaging of inflammatory cells will improve diagnosis and provide a read-out for therapy efficacy. Paramagnetic phosphatidylserine (PS)-containing liposomes were developed for magnetic resonance imaging (MRI) and confocal microscopy imaging of macrophages. These nanoparticles also provide a platform to combine imaging with targeted drug delivery. Results Incorporation of PS into liposomes did not affect liposomal size and morphology up to 12 mol% of PS. Liposomes containing 6 mol% of PS showed the highest uptake by murine macrophages, while only minor uptake was observed in endothelial cells. Uptake of liposomes containing 6 mol% of PS was dependent on the presence of Ca2+ and Mg2+. Furthermore, these 6 mol% PS-containing liposomes were mainly internalized into macrophages, whereas liposomes without PS only bound to the macrophage cell membrane. Conclusions Paramagnetic liposomes containing 6 mol% of PS for MR imaging of macrophages have been developed. In vitro these liposomes showed specific internalization by macrophages. Therefore, these liposomes might be suitable for in vivo visualization of macrophage content and for (visualization of) targeted drug delivery to inflammatory cells.